Evaluating the implementation of the sustainable sites initiative (SITES) and its adaptation potential in China - Fengdi Ma (Environmental and Sustainability Indicators)
The importance of green infrastructure for achieving urban sustainability is increasingly recognized globally. Originating in the United States, the Sustainable Sites Initiative (SITES) is an international green rating system designed to guide sustainable landscape development and evaluate sustainability throughout the entire lifecycle of landscapes and other outdoor spaces. Despite its international scope, the performance of SITES has not been quantified in diverse contexts. Understanding the performance of SITES is crucial for practitioners and regulatory authorities; however, quantitative analysis of previous projects is lacking. Furthermore, the adaptation of SITES in China requires further exploration. This study addresses these gaps by utilizing a dataset of SITES v2 certified projects to examine the achievement of sections and credits across various projects, aiming to understand performance patterns and identify barriers to certification. Performance was assessed using score ratios to measure how effectively projects met potential credits, and Association Rules Mining was employed to explore relationships between related credits. Furthermore, a detailed case study of Beijing Central Green Forest Park was conducted to assess the adaptability and applicability of SITES within the Chinese context. Our findings indicate significant variability in the difficulty of achieving certification across different sections. Among 1166 potential rules, 128 pairs of related credits were identified, suggesting substantive associations among the credits. The case study of Beijing Central Green Forest Park resulted in an overall score ratio of 82%, achieving 171 scores, which underscores the potential of SITES as a valuable sustainability tool in China. However, variability in section performance, particularly lower scores in the Materials Selection section, highlights the challenges faced and emphasizes the need for further adaptations of the SITES criteria to better align with local conditions.